Resistance Exercise Does Not Up-Regulate YAP Expression in Aged Human Skeletal Muscle. (29th May 2020) - Salvador, Amadeo; McKenna, Colleen; Askow, Andrew; Fang, Hsin-Yu; Burke, Sarah; Keeble, Alexander; Alamilla, Rafael; Paulussen, Kevin; Paluska, Scott; Burd, Nicholas
Abstract: Objectives: Yes-Associated Protein (YAP) is implicated as a regulator of the post-exercise skeletal muscle response through mechanical transduction. We recently observed that resistance exercise (RE) increased both total (t) and phosphorylated (p) muscle YAP content, which correlated with extracellular signal-regulated kinase 1/2 (Erk1/2). Other anabolic signaling pathways (i.e., mTORC1) are known to be potentiated by the combined stimuli of RE and protein ingestion during post-exercise recovery. However, the impact of protein ingestion on t- and p-muscle YAP content during recovery from RE is unknown. Therefore, we aimed to determine the nutrient sensitivity of YAP in both an acute and chronic exercise setting in aging skeletal muscle. Methods: Acute study: 13 untrained older women (59.8 ± 0.5 y) were randomized to perform an acute bout of unilateral RE (3 sets × 12 repetitions at 65% of one repetition maximum) followed by the ingestion of whey protein (0.3 g/kg lean body mass) or water. Muscle biopsies of both the rested and exercised legs were collected before and during the postprandial period. Chronic study: 20 untrained middle-aged men and women (47.5 ± 0.3 y) performed 3 weeks of whole body RE (3 d/wk) with moderate or high protein intake set at 1.2 g/kg/d or 1.6 g/kg/d, respectively. Muscle biopsies were taken weekly in the rested state. Total and phosphorylated YAP Ser127 and Erk1/2 Thr202/Tyr204 were examined by western blotting. Results: Acute study: Protein ingestion decreased t- and p-YAP compared to the water condition in the non-exercised leg (main effect: P < 0.04). There was no change in t- or p-YAP, regardless of condition, in the exercised-leg throughout recovery ( P = 0.88). There was no change in p/t ratio of Erk1/2 in the exercised or non-exercised leg. Chronic study: There was no change in either p- or t-YAP in moderate and high protein conditions throughout training (both, P > 0.05). There was a decrease in t-Erk1/2 irrespective of condition ( P = 0.04). There was no change in p/t ratio of Erk1/2 throughout training. There was a significant correlation between t-Erk1/2 and t-YAP (r = 0.741 and P < 0.001). Conclusions: Protein ingestion mediated an acute down-regulation of YAP in the postprandial-state. However, resistance training did not modulate YAP content in aged skeletal muscle tissue. Funding Sources: Funded by Beef Checkoff. AFS is supported by CAPES-Brazil.